Effect of cellulose oxalate as cellulosic reinforcement in ternary composites of polypropylene/maleated polypropylene/cellulose. (July 2020) - Huang, Tianxiao; Kwan, Isabella; Li, Kloce Dongfang; Ek, Monica
Abstract: Micro-sized cellulosic materials are promising reinforcements for thermoplastic composites. In this study, a new type of microcellulose – cellulose oxalate (COX) was used as reinforcement for polypropylene-based composites and its reinforcing effect was evaluated. COX and microcrystalline cellulose (MCC), which was used for comparison, were subjected to ball milling process for different times to obtain milled cellulose powders. Ternary composites consisting of 60 wt% polypropylene (PP) as the matrix, 10 wt% maleic anhydride grafted polypropylene (MAPP) as the coupling agent and 30 wt% milled or non-milled cellulose powder as reinforcement were prepared by melt-extrusion and injection molding. Tensile test results showed that 1 h milled COX-containing composite exhibited the best tensile properties (e.g., tensile strength and Young's modulus are 16.1% and 106.0% respectively higher than those of neat PP) and MCC generally exhibited a poorer reinforcing effect than COX with same milling time.